Analisis Sistem Utilitas pada Bangunan Bandar Udara Suvarnabhumi Bangkok, Thailand - Ulinata (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of the research entitled Analysis of the Utility System at the Bangkok Suvarnabhumi Airport Building, Thailand to provide an overview of the utility system applied to the Bangkok Suvarnabhumi Airport Building, Thailand using a descriptive method by direct observation to the research location, collecting literature studies taken from books, articles that are accessed from the internet and then analyze the data. The results show that Suvarnabhumi Airport Bangkok, Thailand has a fairly good utility system, but some of them need to improve their utility systems such as the Design System for Fire Prevention. Because the better the utility system, the visitors will feel comfortable when in the building and the Architect has succeeded in designing a building where from an architectural point of view, the structure and utility are in accordance with the standard design criteria.